EVALUATING OF FINANCIAL PERFORMANCE AT TIKRIT UNIVERSITY AND ITS IMPACT ON DECISION-MAKING - Enas Nusrat Suleiman (Scholars Digest Publishing, 2024)
The research aims to evaluate the financial performance of the university and analyze it accurately. Analyze various financial indicators such as revenues, costs, and budgets to assess the validity of the university's current financial performance. The simple random method was used to select accountants and administrators at the University of Tikrit for the study sample. The random sample consisted of 300 individuals, and after collecting the questionnaires, 250 questionnaires were received and considered suitable for analysis. The researcher used the descriptive survey method, which was selected for its suitability in this study. The questionnaire data were then analyzed using the statistical program (SPSS version 27). The researcher reached the most important results, including There is a strong positive relationship with statistical significance at a significant level of less than 0.05 between financial performance and decision-making. Through the results, the researcher recommended the following: The need to improve the financial evaluation systems and processes at Tikrit University, including the use of effective financial indicators and standards to measure and analyze financial performance. Develop sustainable financial strategies aimed at enhancing the financial stability of Tikrit University, including diversifying funding sources and improving cost management.